Financial reporting failures, board's competency and effectiveness - Mohd. Sulaiman, Aiman @ Nariman (Palgrave Macmillan, 2013)
Financial misreporting and accounting misstatements figure prominently in recent corporate scandals. Although the more notorious of these involved directors’ fraud and conflict of interests, there are cases that are indicative of a board that has failed to exercise its oversight duty where directors were negligent, resulting in loss or damages to the company. This article highlights the following governance issues: the relevance of financial literacy or expertise and its enforceability and process, and procedures that could improve board's effectiveness. As the cases involving financial reporting failures publicly unfold in courtrooms and in the media, boards and regulators need to rethink and reconsider the suitability of current board practices and regulatory response to governance breakdowns. This article places the discussion within the context of several case studies that deal with specific instances of financial reporting failure and are of interest because of the involvement of and liability risks for non-executive directors. This article is also interesting from a comparative law perspective in view of increasing the number of companies undertaking cross-listing or dual listing of shares. A more consistent approach among the regulators is needed to prevent regulatory arbitrage.